The Analysis On Position Of Security In Architecture - Moosavi, Seyed Mohammad Reza (The Turkish Online Journal of Design Art and Communication, 2016)
The physical comfort is possible through appropriate access to energy and lack of pollution caused by it and living under favorable climatic conditions at suitable temperature and adequate humidity but in many cases spiritual and mental peace and comfort in human depend on the artificial environment in his/her surroundings. Thus human comfort is measured according to three categories of energy, climate, and artificial environment (building and city). The everyday life environment of human in which s/he is immobile and or in move is a space that can be favorable and or intolerable. On the other hand, creating sense of peace and comfort in individual at high levels is related to sense of security in individuals since sense of security may automatically overshadow other human’s requirements and in the case of sense of insecurity, most of senses in human will be reduced and or eliminated. Therefore, it is tried in this article to concern with security as one of the foremost environmental effects on human’s health. To this end, primarily it has been dealt with definition of urban space on the one hand and security on the other hand. Then, after classification of security, the role of urban spaces in sense of insecurity will be explored and finally a case example is proposed that covers security in world comprehensively.
Keywords: Security; Architecture; Urban Space; Secure Space